(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

f(t) = (1/(a^2))(1-e^-at - ate^-at)

2. Relevant equations

f(t) = (1/a)(1-e^(-at))

F(s) = 1/s(s+a)

f(t) = t e^(-at)

F(s) = 1/(s+a)^2

3. The attempt at a solution

F(s) = (1/s(s+a^2)) - (1/(s+a)^2)

Totally lost now, but I think this is wrong anyway, can anyone help me please. I know the answer is

F(s) = 1/(s + a)^2

but I have no idea why.

Kind Regards

Rob K

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Laplace Transform

**Physics Forums | Science Articles, Homework Help, Discussion**